A review on wire arc additive manufacturing: Monitoring, control and a framework of automated system. (October 2020) - Xia, Chunyang; Pan, Zengxi; Polden, Joseph; Li, Huijun; Xu, Yanling; Chen, Shanben; Zhang, Yuming
Highlights: The main challenges for WAAM development were analysed and addressed. The sensing methods used in AM monitoring were reviewed and concluded. The control strategies for both laser AM and WAAM were discussed and concluded. A framework of automated system for WAAM was proposed. Abstract: Wire arc additive manufacturing technology (WAAM) has become a very promising alternative to high-value large metal components in many manufacturing industries. Due to its long process cycle time and arc-based deposition, defect monitoring, process stability and control are critical for the WAAM system to be used in the industry. Although major progress has been made in process development, path slicing and programming, and material analysis, a comprehensive process monitoring, and control system are yet to be developed. This paper aims to provide an in-depth review of sensing and control design suitable for a WAAM system, including technologies developed for the generic Arc Welding process, the Wire Arc Additive Manufacturing process and laser Additive Manufacturing. Particular focus is given to the integration of sensor-based feedback control, and how they could be implemented into the WAAM process to improve its accuracy, reliability, and efficiency. The paper concludes by proposing a framework for sensor-based monitoring and control system for the GMAW based WAAM process. This framework provides a blueprint for the monitoring and control strategies during the WAAM process and aims to identify and reduce defects using information fusion techniques.